2021
DOI: 10.3390/antiox10020280
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Cocoa Bean Shell against Intestinal Damage: An Example of Byproduct Valorization

Abstract: Background: Cocoa bean shell (CBS), a main byproduct of cocoa processing, represents a source of components such as polyphenols and methylxanthines, which have been associated with a reduced risk of several diseases. Therefore, CBS has potential application as a food ingredient. Intestinal mucosa is exposed to immune and inflammatory responses triggered by dietary agents, such as oxysterols, which derive from cholesterol oxidation and are pro-oxidant compounds able to affect intestinal function. We aimed at in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…extract dose-dependently reduced the secretion of both IL-6 and IL-8. Consistent with these results, previous studies have shown that cocoa causes a reduction in IL-8 levels in inflammatory models of colonic epithelial cells [47,48].…”
Section: Plos Onesupporting
confidence: 89%
“…extract dose-dependently reduced the secretion of both IL-6 and IL-8. Consistent with these results, previous studies have shown that cocoa causes a reduction in IL-8 levels in inflammatory models of colonic epithelial cells [47,48].…”
Section: Plos Onesupporting
confidence: 89%
“…Protocatechuic acid is a hydroxybenzoic acid derivate, widely distributed in nature, reported for cocoa beans and related products in several studies [22,23]. Recently, this compound was also described in cocoa bean husks from Peru [30], Colombia [12], Honduras [38], and Ecuador [11,13]. [19] and Cádiz-Gurrea et al [30].…”
Section: Phenolic Acidsmentioning
confidence: 95%
“…Despite the content in proteins, dietary fibers, minerals, and vitamins with nutritional value, CBS also constitutes a potential source of other bioactive compounds, such as polyphenols and methylxanthines [8]. Indeed, several studies have proposed CBS as a low-cost ingredient to develop functional foods, such as bakery [9,10] and dairy products [11] or beverages [12,13]. Furthermore, CBS maintains the aromatic profile characteristic of cocoa that contributes to the pleasant flavor of the final products [14].…”
Section: Introductionmentioning
confidence: 99%
“…Oxysterol is derived from dietary cholesterol which causes dysfunction and epithelium permeability damages on intestinal mucosa by inducing inflammation and ROS overproduction. Cocoa bean shell (CBS) (used alone or within an ice cream) was shown to upregulate nuclear factor erythroid 2 p45-related factor 2 (Nrf2) expression [ 70 ]. Nrf2 is a crucial transcription factor protecting cell response against redox stressors and being modulated by oxysterol [ 71 ].…”
Section: Health Benefits Of Polyphenols and Methylxanthines From Cocoamentioning
confidence: 99%
“…Nrf2 is a crucial transcription factor protecting cell response against redox stressors and being modulated by oxysterol [ 71 ]. Release of interleukin-8 (IL-8) and monocyte chemoattractant protein-1 (MCP-1) induced by oxysterol mixture have been reduced by both CBS and CBS ice cream, confirming the anti-inflammatory potential of cocoa [ 70 ]. Moreover, CBS and CBS ice cream have prevented the decrease of tight junction (TJ) protein levels (Claudin 1, occludin, and JAM-A), which are involved in mucosa permeability.…”
Section: Health Benefits Of Polyphenols and Methylxanthines From Cocoamentioning
confidence: 99%